PERANCANGAN SISTEM LOGIN MENGGUNAKAN PERANGKAT NODE MCU DAN RFID - hartono, rudi (University of Muhammadiyah Tangerang, 2022)
Abstract At one of xyz educational institutions in Tasikmalaya, there is a system, it can be used by users and it can freely access the system as long as they know the address of the site. The problem is with free access of user to the system, then there is a possibility for users who do not have access rights to the system will try to log in and to break into the system. For the irresponsible this will be manipulation or theft of a data. Regarding to that problems, the purpose of this research is to anticipate system login access by designing and building a prototype security system using NodeMcu and RFID technology. The method used in this research is qualitative with the development of agile models, namely Kanban models, while for design using UML models. The final result of this research is a prototype of a login system using NodeMcu and RFID technology as a security alternative to a system on web.